Brand Teasing: How Brands Build Strong Relationships by Making Fun of Their Consumers - Oba, Demi; Howe, Holly S; Fitzsimons, Gavan J (Journal of Consumer Research, 2025)
Abstract Popular brands like Wendy’s, Postmates, and RyanAir have gained notoriety by making fun of their consumers, but is this an effective strategy to build strong consumer relationships? Across 11 (seven pre-registered) studies, using lab data, field data, and a variety of analytical approaches, the current research demonstrates that teasing communication increases consumer engagement with and connection to the brand compared to merely funny or neutral communication. These effects occur because consumers anthropomorphize brands more when they use teasing communication. This leads to greater engagement with brand messages and greater self-brand connection (SBC). We also leverage the interpersonal teasing literature to distinguish between prosocial and antisocial teases and highlight an important boundary condition. Specifically, we demonstrate that while prosocial teasing evokes a positive human schema, antisocial teasing, although still anthropomorphic, activates a negative human schema, which reduces connection to the brand. As a result, antisocial teases lose their relational advantage over purely funny communication. This work contributes to the streams of research on brand humor, anthropomorphism, and consumer–brand relationships. It also provides actionable implications by demonstrating a novel antecedent to consumer–brand connection and the boundaries within which these positive effects are expected to occur.